Enhanced antibacterial activity of silver-decorated sandwich-like mesoporous silica/reduced graphene oxide nanosheets through photothermal effect. (30th January 2018) - Liu, Rong; Wang, Xuandong; Ye, Jun; Xue, Ximei; Zhang, Fangrong; Zhang, Huicong; Hou, Xuemei; Liu, Xiaolong; Zhang, Yun
Abstract: Drug resistance of bacteria has become a global health problem, as it makes conventional antibiotics less efficient. It is urgently needed to explore novel antibacterial materials and develop effective treatment strategies to overcome the drug resistance of antibiotics. Herein, we successfully synthesized silver decorated sandwich-like mesoporous silica/reduced graphene oxide nanosheets (rGO/MSN/Ag) as a novel antibacterial material through facile method. The rGO and Ag nanoparticles can be reduced in the reaction system without adding any other reductants. In addition, the rGO/MSN/Ag showed higher photothermal conversion capacity due to the modification of silver nanoparticles and exhibited excellent antibacterial activities against Pseudomonas putida, Escherichia coli and Rhodococcus at relatively low dosages, which was confirmed by the minimum inhibitory concentration (MIC) test. Meanwhile, the E. coli with a high concentration was selected for exposure using an 808 nm laser, and the antibacterial effect was obviously enhanced by the near-infrared irradiation induced photothermal effect. Moreover, the hepatocyte LO2 were used for the cytotoxicity evaluation, and the rGO/MSN/Ag showed low toxicity and were without detectable cytotoxicity at the antimicrobial dose. As the prepared rGO/MSN/Ag nanosheets have the advantages of low-cost and high antibacterial activity, they might be of promising and useful antibacterial agents for different applications.